Innovations in Service: Probing the Evidence in Sustainable Tourism - Zaim, Ilma; Akbar, Iqbal (School of Business and Management Institut Teknologi Bandung, 2019)
Abstract. Innovation is a critical key to sustainable tourism, as it plays a big part in shaping products and services to be provided in the tourism industry. The competition in sustainable tourism is high due to the discourse to bring positive externalities and the presence of the rent-seeking. This study aims to investigate the innovation process in sustainable tourism by employing a combination of the bibliometric analysis from and systematic review on 91 scientific publications on Web of Science (WoS). A contemporary view of innovation economics is used to approach the analysis. Our research reveals that innovations in most scientific literature are non-radical. Changing the business model is also essential for tourism firms to be more sustainable in the practices. There is a global trend to implement technological innovations in Information and Communication Technologies (ICTs) to pursue the sustainability concept in tourism. Also, our literature review reveals that tourism firms utilise resource-efficient technologies to help to resolve the issues of climate change. Some limitations in investigating the implementation of innovation in sustainable tourism are also discussed. Finally, this study suggests theoretical contributions as well as methodological recommendations for future research.Keywords: Innovation, sustainable tourism, bibliometric study, systematic review